An analysis of tourist carbon footprint in Indonesia – The case of D.I. Yogyakarta - Saputra, Erlis; Sadali, Mohammad Isnaini; Jauhari, Agung (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Tourism is one of Indonesia’s largest economic sectors contributing significantly to the republic’s current development . However, there is a price to pay for developing tourism, namely, the increased generation of CO2 produced by touris and tourism activities which can lead to climate change. To gauge the extent to which this is happening in the country a field study was conducted in D.I. Yogyakarta to determine the amount of carbon produced by individual tourists through tourism activities, and to map the amount of carbon produced by tourists at a tourist destination. The results showed that a) of the total amount of 1,218,416.05 kg of CO2 produced by tourists in the Province of Yogyakarta about 45 percent or 542,971.48 kg CO2 was produced by foreign tourists as compared to 55 percent or 675,444.57 kg CO2 produced by domestic tourists; b) accommodation air conditioning was the biggest carbon contributor with respect to domestic tourists; c) at 5,728.17 kg of CO2 domestic tourists dominated the amount of transportation carbon produced during their stay in D.I. Yogyakarta; and d) the greatest amount of carbon, viz. 236,648.7 kg or 20% of the total CO2 generated by tourists was at the heritage tourism sites.